Wnt signaling in age-related macular degeneration: human macular tissue and mouse model. Issue 1 (December 2015) - Tuo, Jingsheng; Wang, Yujuan; Cheng, Rui; Li, Yichao; Chen, Mei; Qiu, Fangfang; Qian, Haohua; Shen, Defen; Penalva, Rosana; Xu, Heping; Ma, Jian-Xing; Chan, Chi-Chao
Abstract Background The wingless-type MMTV integration site (Wnt) signaling is a group of signal transduction pathways. In canonical Wnt pathway, Wnt ligands bind to low-density lipoprotein receptor-related protein 5 or 6 (LRP5 or LRP6), resulting in phosphorylation and activation of the receptor. We hypothesize that canonical Wnt pathway plays a role in the retinal lesion of age-related macular degeneration (AMD), a leading cause of irreversible central visual loss in elderly. Methods We examined LRP6 phosphorylation and Wnt signaling cascade in human retinal sections and plasma kallistatin, an endogenous inhibitor of the Wnt pathway in AMD patients and non-AMD subjects. We also used theCcl2 −/ − /Cx3cr1 −/ − /rd8 andCcl2 −/ − /Cx3cr1 gfp/gfp mouse models with AMD-like retinal degeneration to further explore the involvement of Wnt signaling activation in the retinal lesions in those models and to preclinically evaluate the role of Wnt signaling suppression as a potential therapeutic option for AMD. Results We found higher levels of LRP6 (a key Wnt signaling receptor) protein phosphorylation and transcripts of the Wnt pathway-targeted genes, as well as higher beta-catenin protein in AMD macula compared to controls. Kallistatin was decreased in the plasma of AMD patients. Retinal non-phosphorylated-β-catenin and phosphorylated-LRP6 were higher inCcl2 −/ − /Cx3cr1 −/ − /rd8 mice than that in wild type. Intravitreal administration of an anti-LRP6 antibody slowed the progression of retinal lesions inCcl2 −/ − /Cx3cr1 −/ − /rd8 andCcl2 −/ − /Cx3cr1 gfp/gfp mice. Electroretinography of treated eyes exhibited larger amplitudes compared to controls in both mouse models. A2E, a retinoid byproduct associated with AMD was lower in the treated eyes ofCcl2 −/ − /Cx3cr1 −/ − /rd8 mice. Anti-LRP6 also suppressed the expression ofTnf -α andIcam -1 inCcl2 −/ − /Cx3cr1 −/ − /rd8 retinas. Conclusions Wnt signaling may be disturbed in AMD patients, which could contribute to the retinal inflammation and increased A2E levels found in AMD. Aberrant activation of canonical Wnt signaling might also contribute to the focal retinal degenerative lesions of mouse models withCcl2 andCx3cr1 deficiency, and intravitreal administration of anti-LRP6 antibody could be beneficial by deactivating the canonical Wnt pathway.